Peran Pembiayaan Mudharabah Dalam Peningkatan Kesejahteraan Ekonomi Masyarakat - Amelia, Nur; Winario, Mohd; Rahmawati, Rahmawati (EL-EMIR Institute, 2025)
This article aims to provide information related to the role of mudharabah financing in improving the economic welfare of society, especially in the MSME and micro entrepreneur sectors. The research method used is the literature research method or literature review. This method focuses on the analysis and synthesis of written works that are relevant to the research topic being investigated. This research shows that mudharabah financing has the potential to provide wider access to capital for MSMEs without fixed interest charges, thereby encouraging business growth and increasing income. Nevertheless, challenges such as the public's low understanding of Islamic finance and the complexity of risk management remain key factors that need to be overcome to maximize the benefits of mudharabah financing.